3-(6x-25)=7(x-3)

Simple and best practice solution for 3-(6x-25)=7(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-(6x-25)=7(x-3) equation:


Simplifying
3 + -1(6x + -25) = 7(x + -3)

Reorder the terms:
3 + -1(-25 + 6x) = 7(x + -3)
3 + (-25 * -1 + 6x * -1) = 7(x + -3)
3 + (25 + -6x) = 7(x + -3)

Combine like terms: 3 + 25 = 28
28 + -6x = 7(x + -3)

Reorder the terms:
28 + -6x = 7(-3 + x)
28 + -6x = (-3 * 7 + x * 7)
28 + -6x = (-21 + 7x)

Solving
28 + -6x = -21 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
28 + -6x + -7x = -21 + 7x + -7x

Combine like terms: -6x + -7x = -13x
28 + -13x = -21 + 7x + -7x

Combine like terms: 7x + -7x = 0
28 + -13x = -21 + 0
28 + -13x = -21

Add '-28' to each side of the equation.
28 + -28 + -13x = -21 + -28

Combine like terms: 28 + -28 = 0
0 + -13x = -21 + -28
-13x = -21 + -28

Combine like terms: -21 + -28 = -49
-13x = -49

Divide each side by '-13'.
x = 3.769230769

Simplifying
x = 3.769230769

See similar equations:

| (3x-1)+(2x+3)*2=82 | | 4((-24+-1x)(3+-1x))=0 | | 18x^3+15x^2-9x= | | 3/4x3 | | 4cos^4x-1=0 | | km^2-c=n | | x^2-14+24=0 | | -13x-20=-11x-120 | | 7-2x/59 | | 110x(14-y)+950y=5740 | | 3.4*t+0.08=11 | | 110(14-y)+950y=5740 | | 3*a+2-5*a=-14 | | -2(2x-6)+9x=6+4(5x-1) | | (4x-9)/(3-4x) | | g=9/5(p-90) | | Log(x)=-3 | | -5x^2+5+10x=0 | | 4x^2+x+17=0 | | 7+(x-3)=6+x | | g(-1)=1-10(-1)-3 | | -64-4a-4=-28 | | 5(3x-2)+5=4-7(2x-1) | | 3x-105=180 | | 8-(3y-3)=6-4y | | ×=70/18 | | 5/4m-8/4 | | 3x^2-60x+120=0 | | -(7w-2z+5y)= | | 7x+8=6-(7x-4) | | 2-10x-5(2+x)=-26 | | 3*1+5=8 |

Equations solver categories